National extension policy and state level implementation: The case of Niger State in Nigeria - Babu, Suresh Chandra; Ogunniyi, Adebayo; Balana, Bedru; Andam, Kwaw S. (International Food Policy Research Institute, 2020)
The aim of Nigeria’s extension reform and transformation agenda through its new national extension policy (NEP) is to put in place a legislated, pluralistic, farmer-responsive, and market-oriented extension system. The reformed extension system aims at an assured and regular source of funding and a well-trained and motivated staff, effectively catering for a variety of actors along targeted value chains. It also aims at effective integration of the complex innovation processes in the agricultural and food system transformation in Nigeria. Implementation of the NEP at the state level remains a major challenge. This paper documents issues, challenges, constraints, and potential solutions and opportunities in implementing NEP at the state level using Niger State as a case study. We use a qualitative method in the context of inclusive consultative process with a focus on the multi-stakeholder participatory model. We found that strengthening actors’ capacities for innovation by considering the complexity of agricultural innovation system is very critical to effective and successful implementation of national agricultural policies in Niger State. We confirm from our study that “networking, partnership facilitation, and collaboration” functions are crucial cross-cutting measures across the agricultural innovation system for operative and systematic implementation of the NEP in Niger State. Based on our findings in Niger State, even if we make effort to draw generic lessons for Nigeria, the case studies show that understanding the dynamics of efficiently and productively implementing the National Extension Policy remain case-specific, and no ‘silver bullet’ can be provided to support agricultural innovation system due to the complex federal governance system in Nigeria. Therefore, a state-level or case-specific is highly recommended for operational implementation process in Nigeria.